2006
DOI: 10.1007/s00109-005-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of DNA methylation: potential applications for disease diagnosis, classification, and prognosis in clinical settings

Abstract: Deregulation of the epigenome is now recognized as a major mechanism involved in the development and progression of human diseases such as cancer. As opposed to the irreversible nature of genetic events, which introduce changes in the primary DNA sequence, epigenetic modifications are reversible and leave the original DNA sequence intact. There is now evidence that the epigenetic landscape in humans undergoes modifications as the result of normal aging, with older individuals exhibiting higher levels of promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 128 publications
1
65
0
1
Order By: Relevance
“…The algorithm development to circumvent the subjective and equivocal interpretation of HOPX expression status including optimal protocols of tissue fixation and staining procedure were required to finally conclude the comparison of the methodologies. On the other hand, Q-MSP can achieve much more objective and specific assessment in a small amount of genomic DNA through PCR amplification using methylation-specific primers and fluorescent probe (Brena et al, 2006). For these reasons, at present, we believe that quantitative assessment of HOPX-b methylation is the preferable method for tumor aggressiveness marker of advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm development to circumvent the subjective and equivocal interpretation of HOPX expression status including optimal protocols of tissue fixation and staining procedure were required to finally conclude the comparison of the methodologies. On the other hand, Q-MSP can achieve much more objective and specific assessment in a small amount of genomic DNA through PCR amplification using methylation-specific primers and fluorescent probe (Brena et al, 2006). For these reasons, at present, we believe that quantitative assessment of HOPX-b methylation is the preferable method for tumor aggressiveness marker of advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Unfortunately there is only a limited probability of methylation for each gene, 24 so only a combined measurement of multiple methylation biomarkers may provide useful data. The M 3 -assay is developed to generate such composite biomarkers.…”
Section: Technical Approachmentioning
confidence: 99%
“…Aberrant DNA methylation is associated with gene silencing or downregulation (Bird, 2002;Dai et al, 2003). Studies of human diseases have revealed that complex diseases such as cancer are often associated with sudden hypermethylation of tumor suppressor genes or hypomethylation of cancer-related genes (Robertson and Wolffe, 2000;Brena et al, 2006). Methylation of the CpG island within the promoter prevents protein binding at DNA methylation sites, directly inhibiting gene transcription because when double-stranded DNA forms a three-dimensional structure, the methyl of methylated cytosine may be highlighted in the major groove, blocking the interaction between transcription factors and genes (Kuroda et al, 2009).…”
Section: Introductionmentioning
confidence: 99%